THE EFFECT OF COMPANY SIZE, SALES GROWTH, CURRENT RATIO (CR), NET PROFIT MARGIN (NPM) AND RETURN ON EQUITY (ROE) ON STOCK PRICES - Nursiam, Nursiam; Rahayu, Vicky Sari (Department of Management, 2019)
This research focuses on how several internal factors influence the company?s stock prices through the company analysis and based on previous studies that have often been done with no consistent results. The purpose of this research is to analyze the size of the company, sales growth, CR, NPM and ROE as a review of the company's share prices on the Indonesia Stock Exchange's LQ45 Index. This research used a purposive sampling technique. Before employing the data analysis, a classic assumption test was performed. The hypothesis testing was carried out using multiple regression analysis. The results showed that the size of the company, sales growth, the NPM, and the ROE affect the stock prices, whereas the CR does not affect stock prices.